The COVID-19 pandemic and mental health of healthcare workers in Serbia - Dzamonja Ignjatovic, Tamara Z; Simonović, Anja; Popović, Dragoslav (Psihološka istraživanja, 2022)
The COVID-19 pandemic was a challenging experience for many professionals worldwide. Healthcare workers particularly took a lot of effort to cope with stressors related to professional challenges that can adversely affect their mental health and cause burnout syndrome. However, it is important to explore the mental health outcomes of the pandemic among healthcare workers in the context of a specific country. This study examined the effects of the increased professional and personal demands on the health workers’ mental health after almost two years of dealing with the pandemic. A cross-sectional online anonymous survey was conducted in October 2021. The sample consisted of 286 healthcare workers (76.7% male) from all regions of Serbia. The questionnaire included socio-demographic data, professional and personal experiences during the pandemic, mental health difficulties, and burnout. The results showed that more than half of the participants experienced a high or moderate level of depressive symptoms, anxiety, and stress. Emotional exhaustion as a symptom of burnout was reported by almost all participants (91.9%), followed by moderate compassion fatigue (60.8%) and a lower level of self-efficiency (23.8%). The most significant predictors of burnout and mental health difficulties were impaired working conditions and insufficient instructions from superiors, a high level of personal concern about infection, and maladaptive coping strategies. The results imply the importance of providing psychosocial support to healthcare workers to prevent further mental health impairments. However, the interventions should be focused on the external organizational factors, instead of addressing solely individual vulnerability.
Keywords: health care workers; COVID-19; mental health; stress; burnout